Can an Infection Hypothesis Explain the Beta Amyloid Hypothesis of Alzheimer’s Disease? - Fulop, Tamas; Witkowski, Jacek M.; Bourgade, Karine; Khalil, Abdelouahed; Zerif, Echarki; Larbi, Anis; Hirokawa, Katsuiku; Pawelec, Graham; Bocti, Christian; Lacombe, Guy; Dupuis, Gilles; Frost, Eric H. (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is the most frequent type of dementia. The pathological hallmarks of the disease are extracellular senile plaques composed of amyloid peptide (Aβ) and intracellular neurofibrillary tangles composed of pTau. These findings led to the “Amyloid beta hypothesis” that proposes that Aβ is the major cause of AD. Clinical trials targeting Aβ in the brain have mostly failed, whether they attempted to decrease Aβ production by BACE inhibitors or by antibodies. These failures suggest a need to find new hypotheses to explain AD pathogenesis and generate new targets for intervention to prevent and treat the disease. Many years ago, the “infection hypothesis” was proposed, but received little attention. However, the recent discovery that Aβ is an antimicrobial peptide (AMP) acting against bacteria, fungi and viruses gives increased credence to an infection hypothesis in the etiology of AD. We and others have shown that microbial infection increases the synthesis of this antimicrobial peptide. Here, we propose that the production of Aβ as an AMP will be beneficial on first microbial challenge but will become progressively detrimental as the infection becomes chronic and reactivates from time to time. Furthermore, we propose that host measures to remove excess Aβ decrease over time due to microglial senescence and microbial biofilm formation. We propose that this biofilm aggregates with Aβ to form the plaques in the brain of AD patients. In this review, we will develop this connection between Infection – Aβ – AD and discuss future possible treatments based on this paradigm.